ANALYSIS OF THE CONCEPT OF EDUCATION IN TAFSIR TARBAWI: A STUDY OF THE TAFSIR BY THE THREE SCHOLARS - Sulastri. A; Charles Rangkuti; Kiki Hardini; Ulil Amri (Indonesian Journal of Islamic Studies (IJIS), 2026)
This study aims to analyze the concept of Islamic education from the perspective of tafsir tarbawi based on the thoughts of the Indonesian three prominent Islamic education scholars, namely Ahmad Tafsir, Abuddin Nata, and Muhaimin. The focus of the study is directed toward three main aspects of education: educational goals, educational materials, and educational methods derived from the values of the Qur’an. This research employs a qualitative approach using library research. The data were obtained from primary sources in the form of the works of the examined scholars and secondary sources consisting of books, journal articles, and relevant research findings. Data collection was conducted through documentation, while data analysis employed content analysis with a descriptive-analytical approach. The results indicate that tafsir tarbawi views the goal of Islamic education as an effort to form insan kāmil, characterized by a balanced development of faith, knowledge, and morality. Educational materials are integrative, combining religious knowledge and general knowledge based on Qur’anic values. Meanwhile, educational methods in tafsir tarbawi emphasize humanistic, contextual, and participatory approaches through exemplification, dialogue, storytelling, and habituation. This study affirms that tafsir tarbawi has strong relevance in addressing the challenges of contemporary Islamic education, particularly in strengthening students’ character and moral values.